IN VITRO SHOOT REGENERATION OF INDONESIAN BANANAS (Musa spp.) cv. AMBON KUNING AND RAJA BULU, PLANTLET ACCLIMATIZATION AND FIELD PERFORMANCE - Yusnita, Yusnita; Danial, Ekawati; Hapsoro, Dwi (AGRIVITA, Journal of Agricultural Science, 2015)
The aim of this study was to observe responses of two banana cultivars âAmbonâ and âRaja Buluâ on different BA concentrations and effects of different media and fertilizer on survival and growth of plantlets.Â  Sterilized explants were cultured on initiation medium (MS with 1mg L-1 BA) for 4 weeks, then subjected to media MS with 2.5, 5.0, or 7.5 mg L-1 BA. Numbers of shoot buds, shoots and propagules were recorded after 4 consecutive passages with 4 weeks intervals.Â  Rooted plantlets were acclimatized in three different media, then treated with or without NPK (32:10:10) fertilizer solution once a week. After 2 months, the survival and growth of plantlets were recorded. Cultures of banana âAmbon Kuningâ showed higher regenerative capacity compared to âRaja Buluâ, producing higher numbers of shoot buds, shoots and propagules. The best medium for propagule proliferation of both banana cultivars was MS+5 mg L-1 BA, producing 40.7 propagules for âAmbon Kuningâ, and 12.3 propagules for âRaja Buluâ per explant. In all acclimatization media tested, 100% of plantlet survival was achieved. The best plantlet growth was found in sand: compost (1:1,v/v) with application of NPK solutions. The in vitro-derived plants were planted in the field and produced fruits of high quality.Keywords: acclimatization, benzyladenine, fertili-zer, genotypes, media mixtures